O posicionamento das/os assistentes sociais brasileiros pela descriminalização e legalização do aborto - Oenning, Thais de Biazzi (2021)
This dissertation has as its object of study abortion and the positioning of the category of social workers in favor of its decriminalization and legalization in Brazil. The research starts from the following question: how was the decision-making process and what tensions occurred in defense of the position of social workers in favor of the decriminalization and legalization of abortion in Brazil? The favorable decision was taken at the 38th National Meeting of the CFESS/CRESS Set, in 2009 in Campo Grande – MS and later at the 39th National Meeting, in 2010 in Florianópolis – SC, after debates within the CFESS/CRESS set. . In order to answer this problem, the general objective was to analyze the decision-making process that supported the position of the professional category of social workers in favor of the decriminalization and legalization of abortion in Brazil. The specific objectives were: to historicize the Brazilian social, economic, political and cultural context and its relationship with the debate on abortion in the professional category of social workers; identify the abortion debate in the Reports and Deliberations of the National Meetings of the CFESS-CRESS group from 2008 to 2019; to apprehend the relationship between social movements and the legalization of abortion in Brazil and its impact on Social Work from the perspective of the ethical-political defense of women's sexual and reproductive rights. Based on the qualitative approach of social research, the work was based on bibliographical, documental and field research. The source of the data was the Brazilian legislation on abortion and professional legislation, reports of the National Meetings of the CFESS/CRESS Joint and interviews carried out with professionals who participated in the management of CFESS in the period, particularly in the Ethics and Human Rights Commission and the presidency, totaling five social workers interviewed. The research highlighted three axes of analysis: problematizing the roots of conservatism in Brazilian society and in the profession; aspects of the renewal of Social Work and the break with conservatism; and the category's political organization process. Based on these axes, the research analyzed the possibility of social workers deliberating favorably for the decriminalization and legalization of abortion in Brazil and the challenges for carrying out this deliberation in the daily professional life in the contemporary context.